UTILIZATION OF LEARNING MEDIA ON SCIENCE MATERIAL IN HIGH CLASS ELEMENTARY SCHOOLS IN THE BALINGGI DISTRICT - Arianti Arianti; Ni Made Mega Hariani; I Wayan Budi Agus Putrayasa (STAH Dharma Sentana Sulawesi Tengah, 2023)
The purpose of this study was to find out the use of learning media in science material in high school elementary schools in the Balinggi District. The type of research used is descriptive qualitative. Data collection techniques used are observation, interviews and documentation. The research results obtained show that most of the high-grade teachers have utilized learning media in natural science material. Types of learning media that are used include: blackboards, torsos, science kits, science learning videos, pictures related to science material, real objects (concrete), environment, printed books, supporting books and LKS books. Barriers commonly experienced by high grade teachers in utilizing learning media such as: limited media, limited time, internet network, not fluent in the use of technology, students are suitable. difficult to set up and difficulties in selecting the media.